Taxation and Production: The Wicksell Analysis - Webb, Ursula K. (Review of Economic Studies, 1934)
Journal Article Taxation and Production: The Wicksell Analysis Get access Ursula K. Webb Ursula K. Webb London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 1, October 1934, Pages 18–30, https://doi.org/10.2307/2967547 Published: 01 October 1934